White matter lesions account for all age-related declines in speed but not in intelligence. - Rabbitt, P; Scott, M; Lunn, M; Thacker, N; Lowe, C; Pendleton, N; Horan, M; Jackson, A (2007)
MRI scans measured white matter lesion prevalence (WMLP) in 65 people ages 65-84 years who also took 17 cognitive tests: 3 tests of general fluid intelligence, 3 of vocabulary, 2 of episodic and 3 of working memory, 2 of processing speed, and 4 of frontal and executive function. Entry of age with WMLP into regression equations as predictors of test scores showed that inferences about the functional relationships between markers of brain aging and cognitive impairments are seriously misleading if they are based on simple correlations alone. A new finding that WMLP accounts for all of the age-related variance between individuals in tests of speed and executive ability but for none of the age-related variance in intelligence revises current hypotheses that gross brain changes affect general fluid intelligence and other mental abilities solely through their effects on information-processing speed.